Rice productivity in Bangladesh: What are you the benefits of irrigation? - Bell, Andrew R.; Bryan, Elizabeth; Ringler, Claudia; Ahmed, Akhter (University Press Limited, 2021)
Agricultural production in Bangladesh has undergone dramatic changes over the past several decades. Green Revolution technologies transformed the agriculture system in the country through the introduction of highyielding rice and wheat varieties, chemical fertilizers and pesticides, and the expansion of tube well-irrigated area, enabling crop production during the dry season (e.g. Hossain 1988; Sen, Mujeri, and Shahabuddin 2004; Timmer 2005). As a result, yields of key staples, namely rice but also wheat, have increased as has food availability. However, serious challenges continue to plague the agriculture sector. These include scarcity of land due to high population density, unbalanced use of fertilizers and pesticides, great variation in water supply across seasons from drought to stagnant flood conditions, resource degradation due to over-application of chemicals and intensive year-round cultivation of rice, climate change and related extreme climatic events.